Pemanfaatan lahan pekarangan untuk mendukung kemandirian pangan di Desa Mundu, Klaten, Jawa Tengah - Perwithosuci, Winny; Andriyani, Nur; Hidayah, Nur; Oftasari, Yosi; Qomarun, Qomarun; Kisnawaty, Sudrajah Warajati (Penamas: Journal of Community Service, 2024)
The planting schedules and harvest quality have changed due to climate change. Consequently, the harvest yields occasionally fail to meet the market's demands and threaten food security. This situation will lead to an increase in food prices and also impact other health issues, such as stunting. Therefore, the aim for food security remains an important project to enhance national development. The community service team from the Muhammadiyah University of Surakarta, in partnership with the Mundu Village Government in Klaten Regency, organized a series of service activities to enhance food security through the "Rumah Tahan Pangan" competition program for the Mundu Village community. The community service agenda included several strategies: socialization, training, and mentorship. The results of these activities indicate that the residents of Mundu Village are willing to support the food security programme. This is illustrated by a 40.6 percent increase in knowledge about food security at the household level, a 5.4 percent increase in knowledge about using yard land, and a 32.4 percent increase in understanding of balanced nutrition.